Geomorphological hazards in a Mediterranean mountain environment - Example of Tétouan, Morocco - Prokos, Hedvig; Baba, Hasnaa; Lóczy, Dénes; El KharimYounes (Hungarian Geographical Bulletin, 2016)
The aim of this paper is to present the geomorphological hazards affecting the city of Tétouan, Morocco. The city is one of the most important urban centres in northern Morocco. Its geographical situation is strongly determined by the fact that in the last centuries it was built on the slopes of two ranges of the Rif Mountains, the Dersa to the North and the Ghorghiz to the South. These slopes relatively abruptly rise above the valley of the river Martil. Leaving the city, the river of only 22 km length flows into the Mediterranean Sea across the relatively wide Martil Plain. Given the geographical and geological setting of this area, heavy precipitation causes several problems during the humid period (November-April). Torrential rainfalls can have devastating effects on the community. Another severe problem lies in the hazard perception by the inhabitants, who lack the necessary information on geomorphic hazards and, as a consequence, keep on building their homes on unstable hillslopes. The working group in which authors participated had the objective to prepare a comprehensive documentation to inform the population on hazards, to make people aware of the vulnerability of the environment they live in.